(untitled) (Revista de Biología Marina y Oceanografía, 2023)
The zoanthid Palythoa caribaeorum secretes a large quantity of mucus that acts as a substrate for microbial communities. Culturable bacteria associated with P. caribaeorum mucus in northeastern Brazil were evaluated through 16S rRNA gene sequences. Proteobacteria was the dominant group, followed by Actinobacteria and Firmicutes. Vibrio was the most common genus, although other groups with the ability to produce biosurfactants and compounds with antimicrobial activity were also present. The studies of culturable marine bacteria may contribute to the understanding of the associated microbial community, opening new opportunities to explore biotechnological potential of microbiota.